The Role of Business Actor in Implementing Japanese Gastrodiplomacy: The Case of AWKitchen Restaurant in Indonesia [Peran Aktor Bisnis dalam Menerapkan Gastrodiplomacy: Studi Kasus Restoran AWKitchen di Indonesia] - Jane Sherly Stephanie; Edwin Martua Bangun Tambunan (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2022)
Business actors as one of the non-state actors play a role in implementing a country's foreign policy, especially in introducing a national image or identity through public diplomacy, which is known as gastrodiplomacy. This article aims to identify and examine the role of a fusion cuisine restaurant in carrying out Japanese gastrodiplomacy in Indonesia. The article is developed from qualitative research applying a case study method. Based on data collecting from interviews, observations, and library research, the Japanese restaurant under investigation is not just a business actor serving fusion cuisine in Indonesia. The restaurant has contributed to showing the positive side of globalization or taming westernization, and its business activities can be categorized as unrecognized gastrodiplomacy. The restaurant has participated in implementing the function of gastrodiplomacy even though without any formal affinity and official recognition from the Japanese government agencies. The fusion cuisine restaurant has succeeded in helping carry out the mission of the Japanese state in introducing its image or identity. Bahasa Indonesia Abstract: Aktor bisnis sebagai salah satu aktor non-negara memainkan peran dalam mengimplementasikan kebijakan luar negeri suatu negara, terutama dalam memperkenalkan citra nasional atau identitas nasional melalui diplomasi publik, yang sering dikenal sebagai gastrodiplomacy. Artikel ini bertujuan untuk mengenali dan menelaah peran dari restoran dengan hidangan kombinasi dalam menjabarkan gastrodiplomacy Jepang di Indonesia. Artikel ini dikembangkan dengan pendekatan kualitatif yang menerapkan metode studi kasus. Berdasarkan data yang diperoleh dari hasil wawancara, observasi, dan studi kepustakaan, restoran Jepang yang diteliti tidak hanya menjadi aktor bisnis yang bertugas untuk menyajikan hidangan gabungan di Indonesia. Restoran ini sudah berkontribusi untuk menunjukkan sisi positif dari Globalisasi atau mengurangi persepsi buruk Westernisasi, dan aktivitas bisnis restoran tersebut dapat dikategorikan sebagai gastrodiplomacy yang kurang mendapat pengakuan. Restoran ini sudah berpartisipasi dalam implementasi fungsi gastrodiplomacy meskipun tanpa perhatian dan pengakuan resmi dari pemerintah Jepang. Restoran hidangan kombinasi telah berhasil membantu membawa misi Jepang untuk memperkenalkan citra atau identitasnya.